KONSERVASI MATA AIR BERBASIS MASYARAKAT DI UNIT FISIOGRAFI PEGUNUNGAN BATURAGUNG, LEDOK WONOSARI DAN PERBUKITAN KARST GUNUNG SEWU, KABUPATEN GUNUNGKIDUL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Spring is as one of the water resources potential that can not be ignored. Gunungkidul district has three physiographic units: Baturagung Hills, Wonosari Basin and Gunung Sewu Karst Hills. All of them affect the distribution of springs in the Gunungkidul Regency. On the other hand, physiography will affect the community adaptation to the environment. It will contribute to the springs conservation effort. The purposes of this research are: 1) to identify the characteristics of springs, 2) to analyze the community participation in conserving the springs as basicinformation to developspring conservation models. To identify the socio-economiccharacteristics and the springs characteristics in the researchareas use a survey method. Unit sampling and analysis is done purposively baseaon three zones: Baturagung Hills, Wonosari Basin and Gunung Sewu Karst. Hills. Socioeconomic survey was done by sampling on the 90 respondents, divided into 3 zones through direct interviews using quetionare. Quantitative descriptive analysis was performed through statistical tests. The results show that the quality of spring water in all physiographic zones meet to the water quality standard, except thosefor colli bacteria. The discharge of karst springs in the hills of Gunung SfJUUgreater than the discharge of the two other zones. The springs distribution is more in Wonosari Basin and Karst Hills of Gunung Sewu than Baturagung Hills. The level of the community participation in springs conservation is mostly done in groups through user spring groups. Generally, socio-economicfactors affect to thelevel of participation in prevention of springs damage.